Aqueous Leaf Extract of Chromolaena odorata Attenuates Methotrexate-Induced Hepatotoxicity in Wistar Rats - Bridget Osamuyimen Ikponmwosa; Usunomena Usunobun (Universitas Muhammadiyah Yogyakarta, 2022)
Methotrexate (MTX) usage, despite its toxicity in body organs, has increased steadily over the years due to its broad applicability for treating different ailments, including various forms of cancer. Certain plant species have been shown to possess therapeutic properties by offering a protective effect against drug side effects. Thus, the current study was carried out to evaluate the potential of aqueous Chromolaena odorata leaf extract (AEOC) to attenuate the effect of MTX-induced hepatotoxicity in Wistar rats. The study divided thirty (30) male Wistar rats into five groups consisting of six each: Group I (control), Group II (AEOC at 250 mg/kg BW), Group III (MTX at 7 mg/kg BW), Group IV (AEOC at 250 mg/kg BW + MTX at 7 mg/kg BW), and Group V (Vitamin C (100 mg/kg BW) + MTX at 7 mg/kg BW). Chromolaena odorata and Vitamin C was administered for ten consecutive days, while MTX was administered on day 8 for three consecutive days. Rats were sacrificed 24hrs after the last administration. Serum collected was used for the determination of Aspartate Aminotransferase (AST), Alanine transaminase (ALT), Albumin (ALB), Total Bilirubin (TB), and Total protein (TP), while liver tissue was used for assessment of Superoxide Dismutase (SOD), Malondialdehyde (MDA) and Catalase (CAT) as well as histopathological analysis. The result showed a significant increase in the level of SOD, CAT and a significant reduction in MDA in Chromolaena odorata or Vitamin C treated groups compared with MTX. Furthermore, Chromolaena odorata or Vitamin C significantly reduced liver function enzymes and Total Bilirubin levels while increasing synthetic molecules compared to the MTX group. Chromolaena odorata attenuated the toxic effect of MTX, which was corroborated by histopathological analysis. In conclusion, Chromolaena odorata attenuated MTX-induced hepatotoxicity by enhancing antioxidant status; thus, scavenging free radicals and reducing oxidative stress.